Preliminary characterization of water quality in the high basin of river Del Valle (Catamarca) - Demin, Pablo Enrique (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2022)
In the province of Catamarca, the basin of river Del Valle is the most important which concentrates populations, agricultural and industrial activity along its route. The objective of this work was measure the quality of water in the upper basin of the river Del Valle is in the initial trainers in this river. The results obtained from the sampling allowed to determine that the quality of the water of this river is generally aceptable for irrigation and consumption. One of the rivers (river Los Puestos) that flow into river Del Valle, have a content of something more arsenic than the rest of the basin, although it does not affect the quality of the river Del Valle, must be considered its existence by the use of this water for irrigation and consumption of the inhabitants of this area.